Analysis of The Marketing Mix Strategy : A Case Study of The Nur Azizah Songkok Recca Enterprise in Bone Regency - Andi Adriyanto Rinaldy; Rahmatullah; Tuti Supatminingsih; Mustari; Muhammad Dinar (Economics and Business Journal (ECBIS), 2026)
Songkok Recca Nur Azizah is a business located in Bone Regency that produces traditional handcrafts in the form of traditional headgear characteristic of the Bugis tribe, South Sulawesi. However, amidst modern market competition, this traditional craft business faces challenges in optimizing its marketing mix strategy. This study analyzes the implementation of the 7Ps marketing mix strategy in the Nur Azizah Songkok Recca Enterprise in Bone Regency, South Sulawesi. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The findings show that the enterprise has implemented the seven elements of the marketing mix, namely product, price, place, promotion, people, process, and physical evidence. Product variety and artisan skills represent the main strengths of the business, while limited digital promotion, conventional payment systems, simple packaging, and a deteriorated business signboard remain key constraints. The study suggests that the enterprise should strengthen digital marketing, adopt cashless payment options, improve product packaging, and renew its physical identity to enhance competitiveness. These findings provide practical insights for culture-based MSMEs seeking to preserve traditional products while adapting to contemporary market changes.